Water diffusion compartmentation at High b values in ischemic human brain - BRUGIERES, Pierre; THOMAS, Philippe; MARAVAL, Anne; HOSSEINI, Hassan; COMBES, Catherine; CHAFIQ, Abdallah; RUEL, Lucile; BREIL, Stéphane; PESCHANSKI, Marc; GASTON, André (American journal of neuroradiology : AJNR, 2004)
We studied the evolution of brain water compartments during the early stage of ischemic stroke. Diffusion-weighted imaging was performed at 1.5 T in 10 volunteers and 14 patients with stroke. We used a single-shot echo-planar technique with 11 b values of 0-5000 s/mm(2). Regions of interest were selected in the white matter (WM) and striatum of the volunteers and in the ischemic core of the patients. Measurements were fitted on the basis of a biexponential decay with the b factor as follows: S(b) = S(0)[(f(slow) x exp(-b x ADC(slow)) + (f(fast) x exp(-b x ADC(fast))] where S(b) is the signal intensity in the presence of a diffusion gradient, S(0) is the signal intensity without diffusion sensitization, ADC(slow) and ADC(fast) are the respective apparent diffusion coefficients (ADCs) of slow diffusing compartments (SDCs) and fast diffusing compartments (FDCs), and f(slow) and f(fast) the respective contributions to the signal intensity of SDC and FDC. In healthy subjects, FDC represents 74.3 +/- 3.1% of brain water, with ADC(fast) = (124.6 +/- 12.0) x 10(-5) mm(2)/s and ADC(slow) = (15.5 +/- 3.9) x 10(-5) mm(2)/s. In stroke, decreased FDC (49.1% +/- 10.9%; P = 1.05 x10(-5)) and increased ADC(slow) ([22.4 +/- 8.1] x 10(-5) mm(2)/s; P = 8.07 x 10(-3)) were observed, but ADC(fast) was not significantly changed ([135.6 +/- 25.7] x 10 (-5) mm(2)/s; P =.151). The restricted diffusion observed in the early stroke is mainly related to a redistribution of water from the FDC to the SDC.